Reforming Mental Health Services for Seriously Emotionally Disturbed Youth Rhetoric, Practice, and Research - Saxe, Leonard; Brandeis Univ., Waltham, MA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
Children with serious emotional disorders receive inadequate and inappropriate services, rather than the comprehensive and coordinated system of care needed. To develop the knowledge needed to provide adequate and appropriate services, an alliance is needed among advocates, practitioners, and researchers. The Mental Health Services Program for Youth, supported by the Robert Wood Johnson Foundation, is a demonstration program intended to develop comprehensive and coordinated systems of mental health care. The community-level projects supported by the program develop such services as case management, emergency services, respite care, and therapeutic foster care. Each project incorporates a plan for integrating services and financial resources for children served by multiple agencies and service systems. A quasi-experimental design is being used to evaluate the program, by context, process, and outcome and by organizational, financial, and client characteristics. The evaluation design involves an interview-based organizational assessment, use of a management information system to assess client data, and a case conference involving input from all members of the clinical team. The importance of bridging the gap between theoretical and empirical knowledge to improve the current delivery system is stressed. (6 tables/figures) (JDD)
Sponsoring Agency: Robert Wood Johnson Foundation, New Brunswick, NJ.
ERIC Note: Paper presented at the Annual Conference of the American Psychological Association (San Francisco, CA, August 16-21, 1991).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agency Cooperation; Child Advocacy; Community Programs; Delivery Systems; Demonstration Programs; Emotional Disturbances; Human Services; Management Information Systems; Mental Health Programs; Program Development; Program Evaluation; Social Change; Systems Approach; Case Management; Robert Wood Johnson Foundation; Speeches/Meeting Papers; Reports, Descriptive; Opinion Papers